การส่งเสริมการขายที่ไม่เป็นธรรมต่อผู้ประกอบการและผู้บริโภค : กรณีศึกษาของประเทศไทย - พงศ์สิน ลัคนากุล (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Nowadays, the business conducts of the entrepreneurs are strong competitive in advertising and sales promotion, for example, sweepstakes, premiums, and price reduction. From this, a legal issue has arisen that whether Thailand has sufficient regulation on controlling the sales promotion, which is considered as unfair trade practice, to protect the fair competition and consumer rights. In this thesis, the researcher studies the theory of sales promotion and laws on the sales promotion concerning consumer protection and competition, by comparing with the laws of the European Union, the laws of the United States of America, and the laws of Japan respectively. It is found that the laws of the said countries clearly specify certain types of sales promotion to be considered as unfair trade practices. There are also several rules to control the sales promotion in many ways. For example, Japan has a law on the value of the premiums, the United States of America has a law controlling the period of time of the sales promotion which includes premiums or price reduction, and the European Union law specifies the types of sales promotion which are considered unfair. However, in Thailand there is only Consumer Protection Act B.E. 2522 regarding the advertising, intending to control the statement shown to the consumers. The Consumer Protection Act does not control the types or methods of sales promotion. For the sweepstakes, the Gambling Act B.E. 2478 only requires that it must have been permitted from the authority before. This is insufficient and unable to control or monitor the sales promotion to be fair to the consumers. For the competitive protection, section 29 of the Competition Act B.E. 2542 only and vaguely mentions the criteria of the unfair trade practices without a clear guideline to follow. Therefore, this thesis suggests that section 29 of the Competition Act B.E. 2542 be amended and apply to control the sales promotion by authorizing the Competition Commission to specify certain types of sales promotion to be considered as unfair trade practices in accordance with the practice of the above mentioned countries.